(untitled) (The Journal of Geography Education in Africa, 2023)
The acquisition of spatial and mountain literacy by children in Tintin in Tibet is related to broader geospatial reasoning which has import later in life. The literature review for this paper covers the theories of spatial literacy and ability, as well as the developing field of mountain literacy. Methodologically, the comic book was analysed in terms of spatial literacy and then mountain literacy, chiefly in terms of altitudinal band differences, risk and danger, through page progression. Key findings were that this particular comic book is full of references to spatial and mountain literacy theories. Young readers who take careful note of the comic book could gain a head start in geography, in particular to what pertains to mountains (climate, vegetation, risk, danger) in Europe and Asia, both lowland and highland, but also in terms of diverse urban and regional forms.